Implementing Systemic Innovation Strategies for a More Sustainable Future: The Case of Three Overseas Countries and Territories - Toffanin, Renato; Jezic von Gesseneck, Milan (Frontiers in Research Metrics and Analytics, 2022)
Addressing sustainability issues requires a radical systemic change across multiple dimensions, including policy, culture, and civil society. This also implies that no blueprints for governing critical sustainability issues both at the local and global levels exist. As a result, rather than imposing decisions, policymakers should engage in a learning process. In this paper, we contend that appropriate policies should be developed and fine-tuned over time through a collective, social endeavour. To support this hypothesis, the study focuses on a shared methodology based on backcasting, a specific type of foresight, to facilitate policy learning (and thus policymaking) within a wide range of territories, regardless of their wealth, geographic characteristics and internal political organisation. This methodology was developed over a three-year period as part of the Territorial Strategies for Innovation (TSI) programme. The overall objective of our assignment was to build capacity and raise awareness within the EU's Overseas Countries and Territories about policymaking and implementation of innovative approaches to development. This innovative approach, which incorporates a systemic innovation perspective, highlights new options and opportunities for adopting and implementing adequate policies to positively impact sustainable development and long-term transformative change. Using empirical examples from Anguilla, Curaçao, and New Caledonia, the paper focuses on the learning processes required to deal with complexity and uncertainty in these remote territories. We conclude by discussing the potential implications of this foresight approach for the sustainable development and transformation of other less-favoured regions and territories.